AdeABC Efflux Pump Controlled by AdeRS Two Component System Conferring Resistance to Tigecycline, Omadacycline and Eravacycline in Clinical Carbapenem Resistant Acinetobacter nosocomialis - Lee, Yi-Tzu; Chen, Hsing-Yu; Yang, Ya-Sung; Chou, Yu-Ching; Chang, Tein-Yao; Hsu, Wei-Jane; Lin, I-Chieh; , ACTION Study Group; Sun, Jun-Ren (Frontiers in Microbiology, 2020)
Carbapenem-resistant Acinetobacter nosocomialis (CRAn) is a significant public health concern. Two novel tetracycline derivatives, omadacycline and eravacycline, may present a treatment option for CRAn. This study investigated the in vitro antimicrobial activity of tigecycline, omadacycline and eravacycline against clinical CRAn isolates and the contribution of efflux pumps in their resistance. Eighty-nine clinical CRAn isolates, including 57 tigecycline non-susceptible ones (Tn-CRAn) were evaluated for minimum inhibitory concentrations (MICs) by the broth microdilution. The relationship between the antimicrobial resistance and efflux pump expression was assessed by their responses to the efflux pump inhibitor 1-(1-naphthylmethyl)-piperazine (NMP). The contribution of the AdeABC efflux pump in their resistance was determined by the complementation of the AdeRS two-component system in wild-type, adeRS operon and adeB gene knockout strains. Among the 89 isolates, omadacycline and eravacycline MICs were correlated closely with those of tigecycline and eravacycline. They demonstrated improved potency, based on MIC90 values, by showing a 4 to 8-fold greater potency than tigecycline. The synergetic effects of tigecycline, omadacycline and eravacycline with NMP were observed in 57 (100%), 13 (22.8%) and 51 (89.5%) of Tn-CRAn isolates, respectively. Further analysis showed that the laboratory strain carrying the Type 1 adeRS operon increased the tigecycline, omadacycline and eravacycline MICs by 4-8 folds, respectively. Eravacycline demonstrated improved potency over tigecycline against populations of CRAn, including Tn-CRAn isolates. The over-expression of AdeABC efflux pumps was directly activated by the AdeRS two-component system and simultaneously reduced the susceptibilities of tigecycline, eravacycline and omadacycline.